Integrasi Visualisasi Sintak Bahasa Pemrograman PHP dengan Sistem LMS - Akhmad Zaini; Hestiningtyas Yuli Pratiwi (SMATIKA JURNAL : STIKI Informatika Jurnal, 2022)
One of the problems that are often faced by beginners in learning programming languages is the complexity of the syntax that must be learned. The Blockly library is a solution that can be taken to reduce programming language syntax errors. With this library, users can simply arrange puzzles and then the puzzle arrangements can be generated automatically into programming language scripts. However, the Blockly library is only a tool for programming penyuntings. For the material to be conveyed to users, we must arrange a good learning path. In order for the material to be structured into a good learning path, we need a learning content processing system or LMS. This study aims to integrate the advantages of the Blockly library with the advantages of the LMS system so that it becomes a good programming language learning medium. The learning path is structured by prioritizing the understanding of syntax writing patterns through a series of simulations, followed by theoretical explanations and discussions. The results of user responses to this learning media show effectiveness of 79%, attractiveness of 81% and efficiency of 81%.